Antirheumatoid Arthritis Activities and Chemical Compositions of Phenolic Compounds-Rich Fraction from Urtica atrichocaulis, an Endemic Plant to China. (11th July 2011) - Wang, Mengyue; Li, Ke; Nie, Yuxiao; Wei, Yingfang; Li, Xiaobo
Abstract : Urtica atrichocaulis, an endemic plant to China, is commonly used to treat rheumatoid arthritis even though its pharmaceutical activities and chemical constituents were not studied. Herein, we reported our investigations on the chemical compositions of the phenolic compounds-rich fraction from U. atrichocaulis (TFUA) and their antirheumatoid arthritis activities. We found that the TFUA significantly inhibited the adjuvant-induced rats arthritis, carrageenin-induced rats paw edema, cotton pellet-induced mice granuloma, and the acetic acid-induced mice writhing response. Our phytochemical investigations on the TFUA resulted in the first-time isolation and identification of 17 phenolic constituents and a bis (5-formylfurfuryl) ether. The extensive HPLC analysis also revealed the chemical compositions of TFUA. Our further biological evaluation of the main phenolic components, individually and collectively, indicated that the antirheumatoid arthritis activities of TFUA were the combined effect of multiple phenolic constituents.